E-008 Endovascular treatment of flow induced anterior spinal artery aneurysm secondary to aortic coarctation. (4th July 2012) - Soltanolkotabi, M; Marden, F; Hurley, M; Shaibani, A; Bendok, B; Batjer, H; Ansari, S
Abstract : Purpose: Neurological complications associated with coarctation of the aorta are generally intracranial. Less familiar, but equally disastrous are the spinal cord complications of this congenital heart lesion. We report on the endovascular treatment of a unique case of a ruptured anterior spinal artery aneurysm caused by a severe, unrepaired, and previously undiagnosed aortic coarctation. Case report/imaging findings: A 56-year-old female with a past medical history of chronic hypertension and coronary artery disease, presented with severe, acute neck pain. Physical examination revealed hypertension, fever, a wide pulse pressure, and aortic regurgitation. Neurological examination was within normal limits at the time of presentation. A CT scan revealed an acute subarachnoid hemorrhage with a small amount of blood in the fourth ventricle and a larger amount at the cisterna magna with extension to the C1 level. CT angiography of the head/neck and spinal MRI/MRA demonstrated an aneurysm ventral to the spinal cord at C6–7, associated with a markedly dilated anterior spinal artery (ASA). The ASA aneurysm was believed to be the source of the subarachnoid hemorrhage. Additionally, a severe aortic coarctation was identified in the thorax. Multiple dilated intercostal spinal collateral arteries communicating with the ASA were noted bypassing the aortic coarctation. The patient rapidly lost consciousness during the CT angiography (GCS=6) and as a result she was intubated. Transfemoral spinal angiography was attempted, but failed due to an inability to access the ascending aorta across the coarctation. The patient was transferred to our tertiary center for further evaluation and treatment. We attempted a spinal angiogram via right transbrachial approach elucidating the 7 mm ASA aneurysm with a wide neck (4 mm) at the C7 level, supplied from a hypertrophied branch of the right thyrocervical trunk. The dome of the aneurysm had an irregular morphology and a daughter sac suggestive of recent rupture. However, endovascular therapy was delayed due to the significant contrast exposure and development of contrast induced nephrotoxicity. Despite our recommendations, aortic coarctation repair was deferred by the cardiothoracic service due to multiple comorbidities. 10 days later, the patient underwent successful endovascular coil embolization of the wide necked ASA aneurysm. Although there was partial encroachment of the parent artery, patent antegrade flow remained secondary to flow demand from this significant collateral route. Summary: In the rare cases of spinal artery aneurysms, caused by the high-flow collaterals bypassing an aortic coarctation, correction of the aortic coarctation will usually lead to regression of these aneurysms. However, in our case, the ASA aneurysm had ruptured resulting in cord compression and progressive myelopathy with risk for re-rupture and devastating complications. A multidisciplinary approach is required to address the multi-faceted treatment plan in these complex presentations including aortic coarctation repair, securing the spinal artery aneurysm via endovascular/microsurgical approach, and balancing the hemodynamics of renal perfusion versus aneurysm stabilization. Competing interests: None.